Effects of Zr/Ti ratio on dielectric and ferroelectric properties of 0.8Pb(ZrxTi1-x)O3-0.2Pb(Co1/3Nb2/3)O3 ceramics - Prasatkhetragarn A. (2014)
The influences of Zr/Ti ratio on electrical properties of the 0.8Pb(ZrxTi1-x)O3-0.2Pb(Co1/3Nb2/3)O3 ceramics prepared by a mixed-oxide method (with x = 0.46, 0.48, 0.50, 0.52, and 0.54) have been investigated in order to identify the morphotropic phase boundary composition in this system. With XRD analysis, the crystal structure of dense specimens appeared to change gradually from tetragonal to rhombohedral with increasing Zr content. The dielectric properties measurements showed a maximum dielectric constant at x = 0.50, while the transition temperature decreased with increasing Zr content in the system. Moreover, all ceramics showed diffused phase transition behaviors with a minimum diffusivity at x = 0.50. In addition, the Polarization-Electric field (P-E) hysteresis loops of the ceramic systems also changed significantly with the Zr content. Interestingly, the loop squareness parameter reached maximum around x = 0.50. Other ferroelectric hysteresis parameters showed noticeable change at x = 0.50. These results clearly showed the significance of Zr/Ti ratio in controlling the electrical properties of the PZT-PCN ceramic systems. © 2008 Elsevier B.V.